Pengaruh Leverage, Kualitas Audit, dan Intensitas Modal Terhadap Tax avoidance - Helmi, Syarif M; Kurniadi, Ahmad (Universitas Bina Sarana Informatika, 2024)
This study aims to examine the effect of leverage, audit quality, and capital intensity on tax avoidance. The method used in this research is Cash Effective Taz Rate (CETR). This method is used to measure tax avoidance. Tax avoidance is a practice carried out by companies using various methods in order to avoid tax obligations. The population used in this study are companies in the Mining Sector for the 2017-2019 period listed on the Indonesia Stock Exchange. Purposive sampling was used in sampling. The number of companies that meet the criteria is 16 companies. This study uses multiple linear regression analysis and T statistical test to answer the hypothesis using SPSS version 25. The results showed that capital intensity has an impact on tax avoidance. Leverage has no impact on the tax avoidance variable and audit quality has no impact on the tax avoidance variable. When viewed from the coefficient of determination indicates that the leverage, audit quality and capital intensity variables explain only about 26.1% of the variation in the tax avoidance variable, while the remaining 73.9% can be explained by other variables.